2011
DOI: 10.1210/en.2011-1004
|View full text |Cite
|
Sign up to set email alerts
|

From Pituitary Expansion to Empty Sella: Disease Progression in a Mouse Model of Autoimmune Hypophysitis

Abstract: Lymphocytic hypophysitis has a variable clinical course, where a swelling of the pituitary gland at presentation is thought to be followed by pituitary atrophy and empty sella. Data in patients, however, are scanty and contradictory. To better define the course of hypophysitis, we used an experimental model based on the injection of pituitary proteins into SJL mice. A cohort of 33 mice was divided into three groups: 18 cases were immunized with pituitary proteins emulsified in complete Freund's adjuvant; six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Although the final condition of IgG4-related hypophysitis has not been reported, Gao et al (37) reported that an empty sella is detected after a long period of treatment with glucocorticoids in cases of autoimmune hypophysitis. Furthermore, development of the pituitary from the expanded state to an empty sella has been reported in a mouse model of autoimmune hypophysitis (38). These data suggest that at least in some cases, IgG4-related hypophysitis results in an empty sella after a stage of swelling.…”
Section: European Journal Of Endocrinologymentioning
confidence: 68%
“…Although the final condition of IgG4-related hypophysitis has not been reported, Gao et al (37) reported that an empty sella is detected after a long period of treatment with glucocorticoids in cases of autoimmune hypophysitis. Furthermore, development of the pituitary from the expanded state to an empty sella has been reported in a mouse model of autoimmune hypophysitis (38). These data suggest that at least in some cases, IgG4-related hypophysitis results in an empty sella after a stage of swelling.…”
Section: European Journal Of Endocrinologymentioning
confidence: 68%
“…In addition, antipituitary antibodies (APA) and antihypothalamus (AHA) are often seen in patients with different pituitary pathologies including hypopituitarism, central hypothyroidism, acromegaly, adenomas, CDI, and in patients with Prader-Willi syndrome associated with hypothalamic dysfunction (13)(14)(15)(16)(17)(18)(19)(20)(21). Likewise, a mouse model of autoimmune hypophysitis showed endocrine dysfunction and disease progression associated with pituitary expansion followed by pituitary atrophy, thus suggesting the existence of a relationship between autoimmunity and endocrinopathy (22).…”
Section: Introductionmentioning
confidence: 99%
“…3,7 Cases of AH with secondary ES have also been reported. 14,15 In our series, we suggested that secondary ES (2/5, 40%) could be the consequence of AHT.…”
Section: Discussionmentioning
confidence: 60%